E-READINESS OF SMES IN ADOPTION OF E-COMMERCE THROUGH LOCAL GOVERNMENT FACILITIES - Bagus Nuari Harmawan (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
When entering a business competition in the digital market, SMEs must have readiness in the use of technology or e-readiness. Readiness to use technology is essential to compete through digital markets that have a broader scope. SMEs in Banyuwangi are trying to enter the digital market by increasing information technology capacity through assistance from the local government through the online marketing website Banyuwangi-mall.com. For this reason, this article attempts to examine the readiness of SMEs to adopt technology (e-readiness) in entering e-commerce facilitated by local governments. This study uses mixed methods by conducting quantitative methods through surveys first. To then be deepened through a qualitative research process conducted with in-depth interviews. The research results show that SMEs that use digital marketing Banyuwangi-mall.com already have a high readiness for technology adoption in the aspects of strategy and management. However, in the aspect of workers, they are still at the middle level, or there are still some shortcomings.